Error Performance of RIS-Assisted Space-Time Coded Network under Time-Selective Fading Environments - Gunel, Hasan Atalay; Yilmaz, Tayfun; Hokelek, Ibrahim; Ilhan, Haci (IEEE, 2024)
This paper investigates the error performance of Reconfigurable Intelligent Surfaces (RIS) assisted communication systems employing two prominent space-time coding techniques, namely Space-Time Block Coding (STBC) and Space-Time Line Coding (STLC), under time-selective fading channels. The STBC (STLC) network comprises a single base station (BS) with two (one) transmit antenna(s) and a user equipment (UE) with one (two) receive antenna(s), respectively. A RIS with N elements facilitates communication between the BS and the UE, particularly in scenarios without Line-of-Sight (LOS) channels. Simulation results reveal that time-selective fading significantly degrades the error performance of space-time coding techniques. However, utilizing RIS in Intelligent mode mitigates these adverse effects by applying necessary phase shift adjustments, thereby improving system reliability in fast-fading environments. In contrast, in Blind mode, the results indicate that the RIS has a minimal impact on improving error performance under fast-fading channel conditions.
Keywords: Reconfigurable Intelligent Surfaces; Alamouti Space-Time Block Code; Space-Time Line Code; Time-Selective Fading Channels; LINE CODE; MIMO; Computer Science; Engineering; Telecommunications